Trypanosoma cruzi infection and/or administration of the nonsteroidal anti-inflammatory nimesulide increase the number of colonic crypts overexpressing metallothioneins in rat colon carcinogenesis - Escalante,R.D. (2006)
Trypanosoma cruzi infection and nonsteroidal anti-inflammatory drugs inhibit colorectal carcinogenesis by mechanisms not completely known and metallothionein proteins (MTs) may be involved in this process. Sixty-six male Wistar rats weighing 90 to 120 g were randomly divided into seven groups (GI to GVII). GI, GII and GIII animals were subcutaneously infected with 200,000 trypomastigote forms of the Y strain of T. cruzi. After 8 weeks, GI, GII, GIV, and GVI were injected with one weekly subcutaneous dose of 12 mg/kg dimethylhydrazine for 4 weeks. In sequence, GI, GIV and GV were treated with nimesulide (10 mg/kg per dose, five times per week for 8 weeks). Groups I, III, IV, and VI had 12 animals, and each of the other groups had 6 animals. All the animals were euthanized 8 weeks after the last dimethylhydrazine injection. The colons were fixed and processed for MT immunohistochemistry. The index of MT-overexpressing colonic crypts (MTEC) was estimated as the percentage of MT-stained crypts in relation to the total number of crypts scored. Five hundred crypts per animal were scored. Data were analyzed by the Kruskal-Wallis test followed by the Dunn test. There was an increase in MTEC index in the groups either infected with T. cruzi or treated with nimesulide or both infected and treated when compared to control (401, 809, and 1011%, respectively). We suggest that the increased formation of MTEC may be related to the protection against carcinogenesis provided both by T. cruzi infection and nimesulide.